Outcomes associated with the use of medications for opioid use disorder during pregnancy. (9th June 2021) - Krans, Elizabeth E.; Kim, Joo Yeon; Chen, Qingwen; Rothenberger, Scott D.; James, Alton Everette; Kelley, David; Jarlenski, Marian P.
Abstract: Aim: To test the effect of the duration of medication for opioid use disorder (MOUD) use during pregnancy on maternal, perinatal and neonatal outcomes. Design: Retrospective cohort analysis of claims, encounter and pharmacy data. Setting: Pennsylvania, USA. Participants: We analyzed 13 320 pregnancies among 10 741 women with opioid use disorder aged 15–44 years enrolled in Pennsylvania Medicaid between 2009 and 2017. Measurements: We examined five outcomes during pregnancy and for 12 weeks postpartum: (1) overdose, (2) postpartum MOUD continuation, (3) preterm birth (< 37 weeks gestation), (4) term low birth weight (< 2500 g at ≥ 37 weeks) and (5) neonatal abstinence syndrome (NAS). Our primary exposure was the duration (count of weeks) of any MOUD use, including methadone or buprenorphine, during pregnancy. Findings: Among 13 320 pregnancies, 306 (2.3%) were complicated by an overdose, 1753 (13.2%) resulted in a preterm birth and 6787 (50.9%) continued MOUD postpartum. Among infants, 874 (7.6%) were low birth weight at term and 7706 (57.9%) were diagnosed with NAS. As the duration of MOUD use increased, we found a statistically significant decrease in the rate of overdose and preterm birth, a statistically significant increase in the rate of postpartum MOUD continuation and NAS and a decline in term low birth weight. Specifically, for each additional week of MOUD, the adjusted odds of overdose decreased by 2% [adjusted odds ratio (aOR) = 0.98; 95% confidence interval (CI) = 0.97, 0.99], preterm birth decreased by 1% (aOR = 0.99; 95% CI = 0.99, 1.00), postpartum MOUD continuation increased by 95% (aOR = 1.95; 95% CI = 1.87, 2.04) and NAS increased by 41% (aOR = 1.41; 95% CI = 1.35, 1.47). The odds of term low birth weight did not change (aOR = 1.00; 95% CI = 0.99, 1.00), although the rate declined with a longer duration of MOUD use during pregnancy. Conclusions: Longer duration of medication for opioid use disorder use during pregnancy appears to be associated with improved maternal and perinatal outcomes.